HUBUNGAN PENGETAHUAN DAN SIKAP SUPIR TRUK KELAPA SAWIT TERHADAP KESELAMATAN BERKENDARA ( SAFETY DRIVING ) DI WILAYAH KECAMATAN BUNTU PANE KABUPATEN ASAHAN - Susilawati Susilawati; Nahidatul Fadhilah R (CV. ADIBA AISHA AMIRA, 2024)
According to data from the Central Statistics Agency (BPS) the number of accidents that occurred in 2019 was 116,411 cases, in 2020 there were 100,028 cases and in 2021 there were 102,645 cases. Even though it is said that every year the number of accidents decreases, accidents are still a large number. Safety driving is the right way of driving, by knowing the proper driving techniques, understanding and following traffic rules so that driving will always be safe and sound and can help to avoid traffic problems. The purpose of this study was to determine the relationship between the knowledge and attitudes of oil palm truck drivers and safety driving. This study used an analytic survey design with a cross sectional approach. A sample of 46 respondents with a total sampling technique of sampling. This study shows that there is a relationship between knowledge (p=0.009) and attitude (p=0.004) with safety driving. It is recommended to increase knowledge and build a good attitude in safety driving.